Chemical Investigation on the Polysaccharides Present in the Mesocarp of Chalkumra (Benincasa hispida) Fruit - Mazumder, Sutapa; ray, Bimalendu; K. Ghosal, Prodyut (Asian Journal of Chemistry, 2010)
The mesocarp tissues of kumra (Benincasa hispida) fruit were homogenized and an alcohol-insoluble residue (BAIR) was isolated. BAIR was rich in carbohydrate (745.4 mg g-1), and contains large amount of pectic substances. The extractable juice (EJ) amounts to 65.9% of the fresh mesocarp tissue and contains, inter alia, pectic polymers, proteins and arabinose. The polysaccharide present in the juice was isolated and characterized by its sugar composition, molecular weight distribution and infrared spectra. It contained 30.6% of galacturonic acid and 69.4% of neutral sugars, mainly galactose, arabinose and glucose. On size exclusion chromatography this pectic substacnce shows almost an asymmetrical peak.